Role of serum magnesium in atrial fibrillation: A study from North Eastern India (International Journal of Biomedical and Advance Research, 2018)
Background: Low levels of serum magnesium have been associated in development of post operative atrial fibrillation (AF) in patients undergoing coronary artery bypass grafting. However, the role of magnesium in the development of AF in ambulatory patients is limited.Aim: To evaluate the relation between serum magnesium levels and presence of atrial fibrillation either paroxysmal or permanent.Material and Methods: Hospital-based prospective observational study, between May 2015 and November 2016 in 100 patients (50 cases and controls each) aged 18years . Admitted patients who had detectable AF on electrocardiography constituted the cases. Patients with any other irregular rhythm , valvular heart disease , history of electrolyte disorder, alcoholism and potassium sparing diuretic use were excluded. Chi-square test, Fisher exact test and Pearson correlation analysis was used to examine the possible relations between serum magnesium level and other parameters . A p value of 0.05 was considered for statistical significance.Results: The mean age 65.39